Hitchhiker’s Guide to Reductive Amination - Podyacheva, Evgeniya; Afanasyev, Oleg I.; Tsygankov, Alexey A.; Makarova, Maria; Chusov, Denis (Synthesis, 2019)
A comparative study of various widely used methods of reductive amination is reported. Specifically, such reducing agents as H2, Pd/C, hydride reagents [NaBH4, NaBH3CN, NaBH(OAc)3], and CO/Rh2(OAc)4 system were considered. For understanding the selectivity and activity of the reducing agents reviewed herein, different classes of starting materials were tested, including aliphatic and aromatic amines, as well as aliphatic and aromatic aldehydes and ketones. Most important advantages and drawbacks of the methods, such as selectivity of the target amine formation and toxicity of the reducing agents were compared. Methods were also considered from the viewpoint of green chemistry.
Keywords: reductive amination; selectivity; atom efficiency; borohydride; hydrogen; palladium; carbon monoxide